Pendampingan Pengolahan Pupuk Organik Limbah Ternak Sapi di Kelompok Ternak Surowani - Putriya Alifia; Lucky Sanjaya; Novian Wely Asmoro; David Maruli Nainggolan; Wahyu Siswanto; Ainur Komariah (IJECS: Indonesian Journal of Empowerment and Community Services, 2022)
ABSTRACTTiyaran, Bulu, Sukoharjo Regency has potential in the agricultural and livestock sectors. One of the service partners is the Surowani who has problems with livestock waste management. The purpose of the service activities carried out by the PPK Ormawa team of Universitas Veteran Bangun Nusantara is to improve the skills of partners in managing livestock waste.. This activity was carried out in several stages, namely mentoring and approaches in the form of discussions, counseling, demonstrations and direct practice related to the manufacture of organic fertilizer from cow dung waste. The results of the service activities concluded that public knowledge about cattle waste treatment increased up to 90%, and the ability to practice composting from cattle waste reached 80%. Keywords: cattle waste, compost, community service, organic fertilizer